Studi Perubahan Karakteristik Kimia Ultisol Palolo Akibat Lama Dan Tinggi Genangan - Muhammad Basir Cyio (Agroland: Jurnal Ilmu-ilmu Pertanian, 2003)
Effects of flooding on chemical characteristic of ultisol soil from Palolo were investigated in the soil science Laboratory Tadulako University. It was discovered that height and duration of flooding increased soil pH, available P, and reduced potential redox (Eh) and the activity of Al-dd and Fe-dd in soil solution.